Revisiting professional translation ethics in Saudi Arabia: a cultural perspective - Shatha Abdullah AlShaye (Humanities & Social Sciences Communications)
Abstract This study aims to revisit the recently constructed Saudi translation ethics (2023) and reassess their validity to guide translators in conveying cultural elements representing Saudi Arabia’s unique cultural heritage. Data from the Diriyah Season Website and Riyadh Season 2023 booklet were analyzed to assess the extent to which dynamic equivalence was attained. The effectiveness of the newly established code of ethics in translating Arabic cultural references into English was evaluated by utilizing Chesterman’s (2001) and Kruger and Crots’ (2014) perspectives on the professional, socio-cultural, and personal dimensions of translation ethics. The findings suggest that the professional code of ethics proved ineffective in guiding translation practices in Saudi Arabia, as it failed to adequately address challenges associated with cultural references, focusing mainly on narrower professional aspects of translation ethics. The study argues that establishing an ethical code for translation in Saudi Arabia requires a foundation rooted in an empirical examination of the ethical issues translators face within the country, among which are cultural challenges. These include cultural challenges shaped by Saudi Arabia’s unique religious, social, and linguistic traditions, which may differ from those encountered in more diverse or multilingual societies. This empirical analysis should also encompass translators’ ethical orientations and their potential ethical engagement as activists within the socio-cultural context.